الديمقراطية بإندونيسيا (JOURNAL OF INDONESIAN ISLAM, 2010)
Democratic system has been implemented in Indonesia for more than ten years. There is no doubt in the success of the implementation of this democracy. However, in fact, the democracy reaches the phase of transition and is in the way of improvement through the democratization of the systems and the rule of law and ethics. This paper deals with this transition processes for maintaining the system and rule of law. The Constitutional Court as a judicial body is independent and autonomous to control laws and regulations. A neutral foreign policy plays a great importance to the increasing role of Indonesia within the ASEAN and the Organization of Islamic Conference. Indonesia has refused to enter into military alliances with other countries, allowing no military bases on its territory, and upholds the principles of peace, stability and democracy at the regional and international levels. The democratization is now challenged by corruption which prevails all over the country and unrest which may happen because of poverty and injustice acts.